2017
DOI: 10.1101/233049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outbreak of invasive wound mucormycosis in a burn unit due to multiple strains of Mucor circinelloides f. circinelloides resolved by whole genome sequencing

Abstract: 40Mucorales are ubiquitous environmental molds responsible for mucormycosis in 41 diabetic, immunocompromised, and severely burned patients. Small outbreaks of 42 invasive wound mucormycosis (IWM) have already been reported in burn units without 43 extensive microbiological investigations. We faced an outbreak of IWM in our center and 44 investigated the clinical isolates with whole genome sequencing (WGS) analysis. 45We analyzed M. circinelloides isolates from patients in our burn unit (BU1) together with 46 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…1,2 In addition to Candida and Aspergillus species as the most common aetiologic agents of nosocomial fungal infections, Candida auris played a significant role in several large outbreaks in different continents. [3][4][5] There is an extensive and expanding list of fungi that have been reported causing healthcare-associated infections, including Pneumocytis jirovecii, 6 Mucor circinelloides, 7 Saprochaete clavata, 8 Exophiala jeanselmei, 9 Sarocladium kiliense 10 and Exserohilum rostratum. 11 Multi-drug resistant yeasts including Candida blankii, 12 Dirkmeia churashimaensis 13 and Candida parapsilosis 14 have also caused outbreaks in intensive care units.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to Candida and Aspergillus species as the most common aetiologic agents of nosocomial fungal infections, Candida auris played a significant role in several large outbreaks in different continents. [3][4][5] There is an extensive and expanding list of fungi that have been reported causing healthcare-associated infections, including Pneumocytis jirovecii, 6 Mucor circinelloides, 7 Saprochaete clavata, 8 Exophiala jeanselmei, 9 Sarocladium kiliense 10 and Exserohilum rostratum. 11 Multi-drug resistant yeasts including Candida blankii, 12 Dirkmeia churashimaensis 13 and Candida parapsilosis 14 have also caused outbreaks in intensive care units.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic fungi are known to spread rapidly worldwide facilitating fast evolution by introgressive hybridization and intragenic recombination amongst lineages in the plant pathogenic ascomycete Fusarium graminearum (O'Donnell et al, 2000). Equally rapidly spreading pathogenicity patterns but in the clinical environment were reported in Mucor circinelloides, one of the major causative agents of mucormycosis (Lee et al, 2014, Garcia-Hermoso et al, 2018. To date, similar studies on the global phylogeographic structure of Lichtheimia are non-existent, although such genetic data are mandatory for preventing the inadvertent intercontinental distribution of highly virulent isolates towards a proper disease management to control outbreaks at a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the ongoing need for large multi-center evaluation studies and standardization, there are also technical developments and improvements in molecular diagnostics. Costs for whole genome sequencing are currently dropping, allowing intensified usage in applied and basic clinical research [ 69 , 70 , 71 , 72 ] as well as outbreak management. For example, Garcia-Hermoso et al, (2018) demonstrated that an outbreak of Mucor circinelloides in a burn unit of a French hospital was caused by cross-transmissions between patients as well as contaminations with a heterogeneous pool of strains from an unknown environmental reservoir [ 72 ].…”
Section: Dna-based Diagnosismentioning
confidence: 99%